MEDIA GAME VISUAL PADA PENYAMPAIAN MATERI PERLINDUNGAN DATA PRIBADI UNTUK MENINGKATKAN PEMAHAMAN KARYAWAN DI PT INFOMEDIA NUSANTARA - Bahrudin, Muhammad; Zulhalim, Zulhalim; Hartawan, Rumadi (Journal of Information System, Applied, Management, Accounting and Research, 2024)
In fact, there are problems that result in a low understanding of the concept of employees at PT Infomedia Nusantara, especially in terms of personal data protection. This is because the approach in delivering material is still too dominated by the Team Leader and the lack of tools for delivering material. So that the ability to think holistically (overall), creatively, objectively and logically cannot be developed. This study aims to design a Visual Novel Game Media for the delivery of Personal Data Protection material to Increase PT Infomedia Nusantara Employees' Conceptual Understanding. The development model used in this research is MDLC (Multimedia Development Live Cycle). With the research design Control Group Pretest-Posttest Design. The results obtained from this study are: 1) The results of increasing employee understanding based on the gain test show that the gain value for the control class is 0,58 and that for the experimental class is 0,71; 2) Employee responses to visual novel game media in the delivery of Personal Data Protection material resulted in an overall average percentage of 91.50% in the "Very Good" category. The conclusion is that the visual novel game media in the delivery of Personal Data Protection material to increase employee conceptual understanding has been developed to be suitable for use as well as to increase employee conceptual understanding.